Социальный класс как фактор дифференциации жизненных шансов - Оксамитная, С.; Бродская, С. (Социология: теория, методы, маркетинг, 2004)
Social classes are salient for the explanation of variations in life chances according to weberian tradition in sociology. Some concepts of life chances in sociology are re viewed, particularly in the modern class analysis. J.Goldthorpe’s class scheme is used to identify individual’s class location. In Ukrainian society now social classes differentiate individual’s life chances much weaker than in the developed capitalist societies. Individuals from all social classes estimate their life chances rather low as a whole. Only slight modification is empirically verified.